Analisis Human Relation, Lingkungan Kerja, dan Kepuasan Kerja Terhadap Kinerja Karyawan pada Super Dazzle Yogyakarta - Kusuma Chandra Kirana; Vira Aliffia Nadya Sivi; Didik Subiyanto (Universitas Batanghari Jambi, 2022)
This observation goals to understand and examine the have an effect on of human relations, work environment and job satisfaction at overall performance of Super Dazzle Yogyakarta personnel. The populace of this observe is the personnel of Super Dazzle Yogyakarta with a total of 55 employees. For the retrieval technique determine Nonprobability Sampling. Saturated Sampling technique is a method of determining the sample if the complete populace of employees is used as a sample, in order that the sample is taken as many as 55 employees. For statistics series the an instrument within the shape of a questionnaire. Methods of facts evaluation using statistical methods such as validity and reliability tests for questionnaires, more than one linear regression evaluation using the classical assumption take a look at for the feasibility of the model; F-test and t-test for hypothesis verification. So the output of this observe shows that: 1) Human relations have no significant impact on the overall performance of Super Dazzle Yogyakarta employees; 2) The work environment has no significant effect at performance of Super Dazzle Yogyakarta personnel; 3) Job Satisfaction has a significant impact at performance of Super Dazzle Yogyakarta employees; 4) Human relations, work environment, and delight have a fantastic and significant influence at overall performance of Super Dazzle Yogyakarta employees. Human relations, work environment, and job pleasure have the capacity to describe the analysis of employee performance variables on average 64.0%, at the same time the ultimate 36.0% cost is the affect of different unbiased variables no longer tested in research.